Essential dermatopathology - Edward, Sara.; Yung, Anthony (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2012)
"Dermatopathology is a very visual specialised field, so we felt it only right that we provide high quality images to help in the learning process - after all 'a picture is a thousand words'. This manual in no ways replaces the knowledge and information obtained by learning and being taught at the microscope or the viewing of many thousands of microscopic samples of skin specimens which one needs to see in order to become proficient at reading dermatopathology specimens. We hope this text book will serve as a helpful quick reference and an aid memoir to help facilitate the understanding of Dermatopathology"--Provided by publisher.
The skin structure and regional differences in the skin -- The cell types in skin structure -- Techniques of dermatopathological biopsies -- Descriptive terms in dermatopathology -- Histochemical stains used in dermatopathology -- Immunohistochemical stains used in dermatopathology -- Immunofluoroscence techniques in dermatopathology -- Epidermis-inflammatory and neoplastic conditions -- Dermis-inflammatory and neoplastic conditions -- Adnexal structures-inflammatory and neoplastic conditions -- Subcutaneous tissue-inflammatory and neoplastic conditions -- Infections and infestations -- Hair and nail- biopsy techniques and disorders -- Cutaneous infiltrates -- Cutaneous soft tissue tumours.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Skin -- Diseases -- Handbooks, manuals, etc; Electronic books